Konflik Sosial terhadap Dampak Budaya Pasola di Desa Wainyapu (International Forum of Researchers and Lecturers, 2025)
This research thinks that Pasola is a series of traditional ceremonies performed by the Sumbanese people who are old enough to have an indigenous religion called Marapu. Every year in February and March, the series does well. The culmination of the traditional ceremonial activities carried out a few days earlier was the so-called Pasola. Pasola was a war fought by both groups of horsemen. Each group consisted of approximately 100 people armed with a spear made of wood with a diameter of approximately 1.5 m whose ends were left blunt The main purpose of this study was to study and describe the social conflict on the impact of Pasola Culture in Wainyapu village. This research also aims to examine and describe the history of Pasola, the purpose of Pasola being implemented, the rules in Pasola and the tribes that participate in Pasola. The concepts that underlie this research are the impact of Pasola, Nyale or sea worms, spears, sandalwood horses, social conflicts, causes of conflicts, forms of conflict, social conflicts and types of conflicts. This study uses a descriptive qualitative research method with a narrative. The data sources needed are primary data and secondary data with observation, interview and documentation data collection techniques. The population in this study is a traditional Rato and there are 3 Rato assistants, using the purposive sample technique. Data analysis using data reduction, data presentation, data verification and conclusion drawn. From the results of the answers obtained in the study, it can be concluded that the data analysis in the family relationship between Pasola participants and the audience is well maintained despite conflicts in it, government supervision and traditional Rato in the implementation of the Pasola tradition to avoid conflicts that occur permanently and well coordinated as well as unity and unity in maintaining this Pasola tradition is well intertwined between Pasola participants. audiences, traditional Rato and even the government in the process of handling conflict resolution has been well minimized.